Solutions of some Linear Volterra Integral Equations by Laplace Transform Method (FULafia Journal of Science and Technology, 2018)
This work provides solutions to some continuous and weakly singular linear Volterra integral equations of thesecond kind by Laplace transform method. Using basic definitions, results and fundamental theorems, Laplace transform method gives an efficient and remarkable performance.Test problems are presented to show the efficiency and reliability of the method.
Keywords: Volterra Integral equations; continuous and weakly singular Kernels; Laplace method